2017
DOI: 10.1021/acs.joc.7b01230
|View full text |Cite
|
Sign up to set email alerts
|

Matsutakone and Matsutoic Acid, Two (Nor)steroids with Unusual Skeletons from the Edible Mushroom Tricholoma matsutake

Abstract: Matsutakone (1), a novel sterol with an unprecedented polycyclic ring system, together with a new norsteroid matsutoic acid (2) were isolated from the fruiting bodies of Tricholoma matsutake. Their structures and absolute configurations were assigned by extensive spectroscopic analyses and computational methods. Bioassay results showed that compounds 1 and 2 exhibited inhibitory activities against acetylcholinesterase (IC 20.9 μM for 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…Edible mushrooms are very popular with the public due to their pleasant taste, low energy, fat content, and health properties [ 1 , 2 ]. Additionally, the extractions of some edible mushrooms display various human health benefits, such as neuroprotective activity, antifatigue ability, improved immunity, cough relief, reduced sputum, and antitumor properties [ 3 , 4 , 5 , 6 ]. In recent years, edible mushrooms have attracted much attention from chemists and biologists because their components contain novel structures and diverse bioactivities.…”
Section: Introductionmentioning
confidence: 99%
“…Edible mushrooms are very popular with the public due to their pleasant taste, low energy, fat content, and health properties [ 1 , 2 ]. Additionally, the extractions of some edible mushrooms display various human health benefits, such as neuroprotective activity, antifatigue ability, improved immunity, cough relief, reduced sputum, and antitumor properties [ 3 , 4 , 5 , 6 ]. In recent years, edible mushrooms have attracted much attention from chemists and biologists because their components contain novel structures and diverse bioactivities.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation coefficient ( R 2 ) ( Figure 4 ) between the experimental and calculated data from linear regression analysis was 0.9991, and the mean absolute error (MAE) and the corrected mean absolute error (CMAE) were 1.3 and 1.0 ppm, respectively, thus supporting the structural rationality of 1 . For absolute configuration, the low cotton effect of electronic circular dichroism forced us to seek help from the optical rotation calculations, which had also been successfully applied in deciding configurations of natural products [ 17 ]. Optical rotation calculations of 1 were carried at the B3LYP/6-31+G (d,p) and B3LYP/6-311++G (2d,p) level, with PCM model in MeOH based on B3LYP/6-31G (d,p) optimized geometries.…”
Section: Resultsmentioning
confidence: 99%
“…matsutake is a very delicious and nutritious wild mushroom from China, where it is considered a medicinal mushroom. The fruiting bodies are a rich source of ergostane derivatives, among which sterol 51 [44], and matsutakone (52) and matsutoic acid (53) [45] are new natural products. Matsutakone (52) shows an unprecedented transposed tetracyclic ring system, whereas matsutoic acid (53) is a C-18 nor-steroid.…”
Section: Separation Of a Chclmentioning
confidence: 99%
“…It has been suggested that both compounds derive biosynthetically from 5,6-epoxy-ergosterol, which was isolated from the same extract. The structures and absolute configurations of 52 and 53 were assigned by extensive spectroscopic analyses and computational methods [45]. Bioassays showed that both compounds exhibited inhibitory activity against acetylcholinesterase (IC 50 20.9 μM for 52) [45].…”
Section: Separation Of a Chclmentioning
confidence: 99%